Paleontological and Spectrometric Characteristics of the Phytoleimmas of Middle-Late Jurassic Plants of the Southeast of Western Siberia; Stratigraphy and Geological Correlation; Vol. 29, iss. 6 - Ivanov V. P. Vladimir Petrovich (2021, 2021)
Title screen